2010
DOI: 10.1016/j.bmc.2009.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial and antileishmanial activities of histone deacetylase inhibitors with triazole-linked cap group

Abstract: Histone deacetylase inhibitors (HDACi) are endowed with plethora of biological functions including anti-proliferative, anti-inflammatory, anti-parasitic, and cognition-enhancing activities. Parsing the structure–activity relationship (SAR) for each disease condition is vital for long-term therapeutic applications of HDACi. We report in the present study specific cap group substitution patterns and spacer-group chain lengths that enhance the antimalarial and antileishmanial activity of aryltriazolylhydroxamates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 46 publications
4
75
0
Order By: Relevance
“…These data imply that potential targets of these compounds also include proteins involved in the assembly of the A complex. Remarkably, compound 24 has an HDAC inhibition activity 15 times higher than that of compound 25 (Table 1; Patil et al 2010), yet both compounds stalled spliceosome assembly to approximately the same extent. Another intriguing observation is the fact that compound 9 (Supplemental Table S1), an analog of 24 with a single methylene chain deletion and a more than eightfold stronger HDAC inhibition than 24 (Chen et al 2008), was not identified as a splicing inhibitor in the primary screen.…”
Section: Screening Of Structurally Diverse Hdacis For Splicing Inhibimentioning
confidence: 97%
See 3 more Smart Citations
“…These data imply that potential targets of these compounds also include proteins involved in the assembly of the A complex. Remarkably, compound 24 has an HDAC inhibition activity 15 times higher than that of compound 25 (Table 1; Patil et al 2010), yet both compounds stalled spliceosome assembly to approximately the same extent. Another intriguing observation is the fact that compound 9 (Supplemental Table S1), an analog of 24 with a single methylene chain deletion and a more than eightfold stronger HDAC inhibition than 24 (Chen et al 2008), was not identified as a splicing inhibitor in the primary screen.…”
Section: Screening Of Structurally Diverse Hdacis For Splicing Inhibimentioning
confidence: 97%
“…However, the exact relationship between zinc chelation, protein acetylation state, and splicing inhibition is not clear, as only a limited set of HDAC inhibitors (HDACis) was screened. In the present work, we sought to clarify this relationship by screening a HDACi library that was structurally more diverse (Chen et al 2008;Canzoneri et al 2009;Oyelere et al 2009;Mwakwari et al 2010a,b;Patil et al 2010). We report here the elucidation of unique molecular features that confer splicing inhibition upon zinc-chelating agents with HDAC inhibition activity.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Amongst the various classes of nitrogen heterocycles, 1,2,3-triazoles and their derivatives deserve special recognition due to their wide usage in industrial applications as dyes, photographic materials, corrosion inhibitors and as herbicidal, fungicidal and antibacterial agrochemicals [5,6]. Several members of the 1,2,3-triazole family exhibit a broad spectrum of antiinfectious properties such as antimicrobial [7], anti-HIV [8], anti-allergic [9] and antimalarial activities [10]. On the other hand, 2(1H)-pyrimidinones also show significant biological activities [11].…”
Section: Introductionmentioning
confidence: 99%